To r or not to r: social correlates of /ɹ/ in Singapore English - Tan, Ying Ying (2013)
This paper seeks to determine the correlation between the occurrences of postvocalic-r, intrusive-r and linking-r in Singapore English (SgE) and the users’ education levels and socioeconomic status. This paper will also investigate the attitudes that SgE speakers hold toward the use of postvocalic-r and intrusive-r in the language. The results show that there is a direct correlation between the education level and socioeconomic status of the speaker and the production of postvocalic-r and intrusive-r in SgE. Speakers of higher education levels and socioeconomic status have a tendency to produce the postvocalic-r; speakers of low education levels and socioeconomic status have a tendency to produce the intrusive-r. The attitudes test also shows that users of postvocalic-r are viewed more positively as compared to users of intrusive-r. The results suggest that postvocalic-r and intrusive-r are not simply concrete, categorical phonological processes, but that their uses are motivated by social factors.